Living apart together over long distances – time-space patterns and consequences of a late-modern living arrangement - Reuschke, Darja (ERDKUNDE, 2010)
In this paper people living apart together at a greater distance with his/her partner (long distance LATs) are investigated, using empirical evidence from Germany. Previous research did not differentiate between couples that live apart over a long distance or in close proximity. In official statistics and surveys across Europe and North America, the spatiality of LAT unions is not captured either. The present results, which are based on a random sample survey of people who recently moved to selected metropolises, reveal that distance matters in this respect: Long distance LAT unions are not only associated with specific formation and motivation contexts, but also with distinctive socio-structural characteristics compared to couples in separate households close-by. Long distance LATs are young, spatially mobile, and highly skilled, and most frequently the living arrangement is due to labour market constraints. LATs are altogether a small population segment in late-modern societies, however, they are concentrated in metropolitan regions and cities, which points to the need of contemporary population, housing and urban studies to pay attention beyond the household to the level of living arrangements in order to understand how societal change shapes urban landscapes and which role it plays in transforming urban space. To be more precise, considering long distance LATs contributes, for instance, to our understanding of the relocation/residential behaviour of highly qualified couples, tenure choice behaviour, and preferences for specific dwelling features.